Urban rainwater resource utilization: A sustainable environmental impact assessment using life cycle assessment (LCA) and water balance model - Xiande Hu; Fenfei Gu (Desalination and Water Treatment)
Urban water management is facing significant challenges due to rapid urbanisation and climate change, such as increased water demand and reduced water availability. To address these issues, this study aims to optimise urban stormwater resource use strategies by developing an integrated assessment framework that combines Life Cycle Assessment (LCA) and Stormwater Management Modelling (SWMM). This framework quantifies the environmental impacts of various stages of stormwater use and simulates the dynamics of water resources. A case study conducted in Wenzhou, a coastal city in eastern China with a population of over 9 million, showed that rain gardens scored highly in terms of both environmental (0.8) and social satisfaction (0.75). The study concludes that the integrated evaluation framework can effectively reflect the environmental impacts and resource efficiency of urban rainwater resource utilisation, and is important for promoting the sustainable development of urban water resource management.